Impact of Governance on Foreign Direct Investment in Arab Countries - Al-Murshed, Sultan; Al-Zamami, Murad; Mahdi, Saifaldeen (Jordan Journal of Business Administration, 2016)
This study aims to examine the relationship between governance and foreign direct investment. The empirical investigation employs a panel dataset of 12 Arab countries over the period (1996-2010), which have been characterized by relative political stability over subsequent years. To do so, the impacts of six governance indicators, developed by the World Bank, on foreign direct investment are checked. We start by applying the Hausman test that suggests the appropriateness of the fixed effect model. The findings revealed that the government effectiveness indicator and the regulatory quality indicator are the most important factors affecting the attraction of foreign direct investment in the studied sample. On the other hand, the other four governance indicators; namely, control of corruption, political stability, absence of violence and rule of law and voice and accountability have no significant effects on foreign direct investment. These results highlight the need for active efforts to improve governance in Arab countries. Such measures will certainly ameliorate the attractiveness of foreign direct investment, considered as an important engine for enhancing economic growth and sustainable development.